The influence of anxiety, hostility and type D personality on health behaviors of university students - Artemisa R. Dores; Débora Barros; Ana Brito; Suveer Singh; Ricardo Teixeira (Saúde & Tecnologia, 2018)
Interest in type D personality and negative emotions such as anxiety and hostility has been growing. These factors are associated with health risk behaviors, which could determine the incidence and progression of cardiovascular disease in initially healthy individuals. We sought to evaluate the prevalence of anxiety, hostility and type D personality and its influence on health risk behaviors in a cohort of university students. One hundred and fifty-one students completed five questionnaires. Mixed methodology using Pearson’s correlation, and regression analysis determined associations between risk factors and health behaviors. We observed a mild hostility and anxiety disturbance (M=0.95; SD=0.61 and M=0.91; SD=0.70). Type D personality was present in 37.7% of the participants. There was a positive association between hostility and smoking (r=0.168; p=0.04), alcohol (r=0.215; p=0.008) and coffee consumption (r=0.280; p=0.000), as well as a negative association between hostility and anxiety (r=-0.263; p=0.001), type D personality (r=-0.194; p=0.017) and lifestyle (r=-0.306; p=0.000). Besides gender variables, alcohol consumption, coffee intake, physical exercise, diet and type D personality assumed statistical relevance explaining the health behaviors (p<0.05). Based on these results we argue that college students may benefit from a premature evaluation for the prevention of future cardiovascular disease.